Biosynthesis and biocompatibility evaluation of zinc oxide nanoparticles prepared using Priestia megaterium bacteria - Mona A. Ashour; Basma T. Abd-Elhalim (Scientific Reports, 2024)
Abstract The current study aimed to find an effective, simple, ecological, and nontoxic method for bacterial green synthesis of zinc oxide nanoparticles (ZnONPs) using the bacterial strain Priestia megaterium BASMA 2022 (OP572246). The biosynthesis was confirmed by the change in color of the cell-free supernatant added to the zinc nitrate from yellow to pale brown. The Priestia megaterium zinc oxide nanoparticles (Pm/ZnONPs) were characterized using UV–Vis spectroscopy, high-resolution transmission electron microscopy (HR-TEM), energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), and zeta potential. The Pm/ZnONPs characterization showed that they have a size ranging between 5.77 and 13.9 nm with a semi-sphere shape that is coated with a protein-carbohydrate complex. An EDX analysis of the Pm/ZnONPs revealed the presence of the shield matrix, which was composed of carbon, nitrogen, oxygen, chlorine, potassium, sodium, aluminum, sulfur, and zinc. The results of the FTIR analysis showed that the reduction and stabilization of the zinc salt solution were caused by the presence of O–H alcohols and phenols, O=C=O stretching of carbon dioxide, N=C=S stretching of isothiocyanate, and N–H bending of amine functional groups. The produced ZnONPs had good stability with a charge of − 16.2 mV, as evidenced by zeta potential analysis. The MTT assay revealed IC50 values of 8.42% and 200%, respectively, for the human A375 skin melanoma and human bone marrow 2M-302 cell lines. These findings revealed that the obtained Pm/ZnONPs have the biocompatibility to be applied in the pharmaceutical and biomedical sectors.